2020
DOI: 10.11591/eei.v9i3.2004
|View full text |Cite
|
Sign up to set email alerts
|

Decision support system for determining chili land using weighted product method

Abstract: Chili is one of the most consumed food commodities in Indonesia. Thus, chili is very influential to the economic, also inflation and deflation of an area. In order for the needs of chili to be fulfilled and to be able to export, the production must be increased with one consideration being the selection of the right land. The right land must meet the criteria agreed upon by experts, there is land height, soil pH, nutrient value and ambient temperature. This research aims to create a system to support the decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
6
0
2
Order By: Relevance
“…Meanwhile, K4 (meeting new people) and K5 (adventure-seeking) have the lowest priority value, while K1 (self-actualization) and K9 (destination image) have the middle 0.080 0.080 0.000 0.080 0.080 0.080 0.080 0.080 0.080 0.080 0.000 0.000 0.204 0.080 K2 0.111 0.056 0.056 0.111 0.111 0.111 0.111 0.111 0.111 0.111 0.000 0.000 0.000 0.000 K3 0.100 0.100 0.043 0.100 0.100 0.100 0.100 0.100 0.100 0.100 0.000 0.000 0.000 0.060 K4 0.077 0.077 0.059 0.110 0.077 0.110 0.110 0.110 0.078 0.110 0.000 0.000 0.000 0.078 K5 0.000 0.275 0.186 0.000 0.000 0.000 0.000 0.234 0.230 0.000 0.000 0.000 0.000 0.075 K6 0.112 0.000 0.000 0.153 0.000 0.121 0.153 0.153 0.153 0.153 0.000 0.000 0.000 0.000 K7 0.073 0.000 0.000 0.073 0.073 0.073 0.073 0.073 0.102 0.073 0.071 0.000 0.181 0.132 K8 0.000 0.134 0.000 0.000 0.000 0.118 0.134 0.000 0.000 0.000 0.160 0.136 0.158 0.159 K9 0.065 0.120 0.000 0.120 0.065 0.065 0.065 0.065 0.065 0.065 0.063 0.000 0.120 0.120 Table 10 shows three different scenarios of the criteria priority scale input. Recommendation result; Tables [11][12][13] shows the comparison results of manual FAHP calculation, the DSS' FAHP calculation, and the AHP calculation for all of the scenarios. Table 11 points out the recommendation sequence of the two methods are different.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Meanwhile, K4 (meeting new people) and K5 (adventure-seeking) have the lowest priority value, while K1 (self-actualization) and K9 (destination image) have the middle 0.080 0.080 0.000 0.080 0.080 0.080 0.080 0.080 0.080 0.080 0.000 0.000 0.204 0.080 K2 0.111 0.056 0.056 0.111 0.111 0.111 0.111 0.111 0.111 0.111 0.000 0.000 0.000 0.000 K3 0.100 0.100 0.043 0.100 0.100 0.100 0.100 0.100 0.100 0.100 0.000 0.000 0.000 0.060 K4 0.077 0.077 0.059 0.110 0.077 0.110 0.110 0.110 0.078 0.110 0.000 0.000 0.000 0.078 K5 0.000 0.275 0.186 0.000 0.000 0.000 0.000 0.234 0.230 0.000 0.000 0.000 0.000 0.075 K6 0.112 0.000 0.000 0.153 0.000 0.121 0.153 0.153 0.153 0.153 0.000 0.000 0.000 0.000 K7 0.073 0.000 0.000 0.073 0.073 0.073 0.073 0.073 0.102 0.073 0.071 0.000 0.181 0.132 K8 0.000 0.134 0.000 0.000 0.000 0.118 0.134 0.000 0.000 0.000 0.160 0.136 0.158 0.159 K9 0.065 0.120 0.000 0.120 0.065 0.065 0.065 0.065 0.065 0.065 0.063 0.000 0.120 0.120 Table 10 shows three different scenarios of the criteria priority scale input. Recommendation result; Tables [11][12][13] shows the comparison results of manual FAHP calculation, the DSS' FAHP calculation, and the AHP calculation for all of the scenarios. Table 11 points out the recommendation sequence of the two methods are different.…”
Section: Resultsunclassified
“…The FAHP method had been applied to tourism decision support systems to recommend tourist destinations. Istianto et al [13] designed a DSS of beach tourism objects in Gunungkidul, Yogyakarta, with eight assessment criteria (distance, price, safety, population, cleanliness, uniqueness, terrain, and facilities). Overbeek et al [14] built a recommendation system for choosing tourist destinations in Kupang City using the Weighted Product method with three assessment criteria (price, facilities, and reviews of tourists).…”
mentioning
confidence: 99%
“…Flowchart is a showing chart a flow or flow in a program or logical procedures, where flowcharts are much needed in order to simplify the way to understand a system flow that will be built [26]. The system will work when the DHT11 sensor detects the temperature and humidity of the enclosure environment, based on the predetermined temperature value set on the microcontroller.…”
Section: Flowchartmentioning
confidence: 99%
“…The method used in this study is the simple additive weighting (SAW) method with the weighted product (WP) method. Based on the background described above, a DSS is needed using the "WP method and SAW method to select Majalaya superior carp brooders" as the best solution recommendations [9]- [12]. Previous studies related to this research include; Research conducted in 2019 [11] used the WP method with criteria such as size, weight, color, physical defects, and even water conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies related to this research include; Research conducted in 2019 [11] used the WP method with criteria such as size, weight, color, physical defects, and even water conditions. The results showed that the criteria for size, weight, color, physical defects, and even water conditions could help catfish [12] the process of making a DSS for land selection for chili plants with the WP method with predetermined criteria and weights. Based on the results of testing the WP calculation system with manual calculations, the final results are almost the same with an accuracy of 97.6%.…”
Section: Introductionmentioning
confidence: 99%